DINAMIKA KEJADIAN DEMAM BERDARAH DENGUE DENGAN PENDEKATAN SPASIO-TEMPORAL DI KECAMATAN MARITENGNGAE, KABUPATEN SIDENRENG RAPPANG, PROVINSI SULAWESI SELATAN TAHUN 2008-2009 - , I Made Swastika, dr. Tribaskoro Tunggul Satoto, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Dengue Hemorrhagic Fever (DHF) causes 40% of world population at risk for infection and every year 50 million people get infected and as many as 24,000 die. Incidence rate in Indonesia, particularly at subdistrict of Maritengngae, District of Sidenreng Rappang, Sulawesi Selatan is increasing, so that neet to controlled. Disease distribution has not been documented regionally. The dynamics of the incidence that comprises characteristics of the patient, environmental condition, susceptibility of mosquitoes by use of insecticide consequence, transovarial ineffectiveness and the incidence pattern are unknown. Objective: To identify the incidence of DHF through spatio-temporal approach, comprising gender, age, the habit of keeping water container clean, house density and the availability of water container within the radius of 100 meters from the house of the patient, resistance of the mosquito and transovarial tranmission of dengue virus. Method: The study was observational with cross sectional design. Subject of the study were DHF patients. Analysis used chi square, independent T-test, retrospective space-time, absorbent value (AV) deviation standard and transovarial transmission index (TTI). Result: Incidence distribution in 2008-2009 for gender showed no difference (p=1.000), age <15 years differed from age â¥15 years (p=0.016 and 0.013), house density and availability of water container around the house of the patient showed no difference (p=0.829 and 0.538). The habit of cleaning water container at the house of the patient was 43.84%. Aedes aegypti had medium resistance (1.94%) and contained dengue virus (TTI=33.33%). Conclusion: There was no difference in the distribution of gender and house density and availability of water container around the house of the patient, but there was difference in age group in the incidence 2008-2009. Only a part of the patient house with habit of cleaning water container. There were insecticide resistance and transovarial tranmission of dengue virus in Aedes aegypti mosquito.